2018
DOI: 10.1177/0009922818787329
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Attention-Deficit/Hyperactivity Disorder and Comorbidities in a Diverse, Urban Primary Care Setting

Abstract: We tested the accuracy of 2 parent-report tools, the Pediatric Symptom Checklist (PSC-35) and Child Behavior Checklist (CBCL), to identify attention-deficit/hyperactivity disorder (ADHD) and distinguish complex (highly comorbid) cases in an urban, largely Latino pediatric practice. Spanish- and English-speaking parents of children aged 6 to 10 years completed a PSC-35 and CBCL at well visits. Those with CBCL Attention Problems Subscale (CBCL-APS) T scores ≥60 plus controls completed the diagnostic MINI-KID (Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…32 Over the years, several authors have suggested that the PSC-ES and PSC-AS cutoff scores might not be sensitive for detecting ADHD and/or behavioral disorders and alternate cutoff criteria have been suggested. 21,[33][34][35][36] All of these studies are based on the results from the PSC-17-P and may not be equally translated to the youth-completed version. Furthermore, there are no studies that evaluate the cutoff scores, sensitivity, specificity, or positive predictive value of the PSC-17-Y.…”
Section: Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Over the years, several authors have suggested that the PSC-ES and PSC-AS cutoff scores might not be sensitive for detecting ADHD and/or behavioral disorders and alternate cutoff criteria have been suggested. 21,[33][34][35][36] All of these studies are based on the results from the PSC-17-P and may not be equally translated to the youth-completed version. Furthermore, there are no studies that evaluate the cutoff scores, sensitivity, specificity, or positive predictive value of the PSC-17-Y.…”
Section: Screeningmentioning
confidence: 99%
“…34,39 • Re-administrating the PSC-17-Y at follow-up assessments is helpful as it provides objective evidence for changes over time. Literature suggests that the PSC global score and subscale scores could help track treatment progress and outcomes 4,35,36 ; however, further research is needed to confirm this before making it a standard of care in clinical practice. • Finally, this model is even more relevant to the overall welfare of adolescents during the COVID-19 pandemic, given the increased mental health needs of adolescents, especially in socioeconomically disadvantaged communities that have been disproportionately impacted.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…The data for this study was collected from well-child visits at the Pediatric Unit of the Massachusetts General Hospital Chelsea Healthcare Center (MGH Chelsea) in Chelsea, MA. 41 The clinic is located in Chelsea, MA, which is one of the most densely populated cities in the country and home to a significant immigrant population, particularly Spanish-speaking.…”
Section: Methodsmentioning
confidence: 99%
“…The number of CBCL subscale elevations has been utilized as a marker of general psychiatric impairment in prior literature. 41 We determined this to be a general yet robust measure of potential psychiatric problems in our sample.…”
Section: Primary Outcome: # Of Subscale Elevationsmentioning
confidence: 99%
See 1 more Smart Citation